Role of vacuolating cytotoxin in gastritis due to Helicobacter pylori in gnotobiotic piglets. - Eaton, K A (1997)
To investigate the role of the Helicobacter pylori cytotoxin in the pathogenesis of gastritis, gnotobiotic piglets were colonized with either toxigenic H. pylori or a nontoxigenic isogenic mutant. Only piglets given the toxigenic strain developed toxin-neutralizing antibodies (indicating that toxin is expressed in vivo), but there was no difference in bacterial colonization, epithelial vacuolation, or gastritis between the two groups of piglets.